Composition of fatty acids by gas chromatography, physicochemical, sensory quality, and index of quality tapioca lipids enriched with okara - PRIULLI, Érica; COSTA, Douglas Martins da; SILVA, Clemilson Antonio da; PIRES, Caroline Roberta Freitas (Food Science and Technology, 2025)
Okara is a by-product of soybeans containing protein, fiber, and fatty acids. However, it is rarely used. This research proposed the use of okara flour in tapioca formulations. It aims to identify the physicochemical and technological aspects of the tapioca-added okara flour and quantify the fatty acid content of the formulations to determine their nutritional lipid quality and evaluate their acceptability. The study compared a standard cassava starch formulation (SF) with four tapioca formulations replaced partially by okara flour in 15% (F15), 30% (F30), 40% (F40), and 50% (F50). The analyses conducted included microbiological, physicochemical, technological composition, fatty acid, and intention to purchase. The addition of okara flour increased lipids, proteins, fibers, moisture, ash, luminosity, reddish and yellowish color, and water and oil absorption indexes. Additionally, okara flour improved the nutritional lipid quality as indicated by the atherogenicity index, thrombogenicity index, hypocholesterolemic/hypercholesterolemic ratio, and polyunsaturated/saturated ratio. These improvements in the nutritional and technological characteristics of the flour mixtures suggest promising potential for the traditional Brazilian tapioca partially replaced with okara flour, as evidenced by the similarity in purchase intention among SF, F15, F30, F40, and F50 formulations, with no statistical differences in purchase intention.